State's Responsibility to Respect Constitutional Guarantees of the Rights of the Accused - Abdullah Muhammad, Hemn; Hasan Baram, Muhsin; Hamed Darwesh, Delshad (International Journal of Psychosocial Rehabilitation, 2019)
The subject of human rights and its guarantees has now become one of the basic demands of the peoples, especially after the changes witnessed in the political systems of the Arab countries in the period (2003- 2010) called the Arab Spring, and those that followed in the collapse of some repressive political regimes in the Middle East. These changes in the countries reached by the spring have been instrumental in consolidating the concept of individual rights and freedoms, especially those relating to the accused as the weak party to the criminal case. Governments that came to power after the changes had to reinforce this concept and prove to their people that they believed in their constitutions, since the Constitution was the most powerful and supreme source of protection for fundamental rights and freedoms - particularly the rights of the accused in the criminal case. However, the State is the only side that translates this protection prescribed in the Constitution; for that the Iraqi Constitution of 2005 has been devoted chapter II for this subject (rights and freedoms) in articles (14-46) in addition to Article (13).Iraq has ratified many international conventions related to this subject according to the special law on ratification of International Conventions and Treaties No. (111) of 1979, making Iraq at the forefront of the States that respect the individual rights and freedoms, including the rights of the accused. In order to translate these guarantees into reality, we must activate the issue of monitoring the legitimacy of the actions taken by the state during the course of the criminal case, in addition to monitoring the constitutionality of laws, which is a legal mechanism to verify the conformity of laws with the Constitution.